The The impacts of green areas distributive injustice on marginalized population in the context of Covid-19 - Tang Valdez, Andrea (2021)
This paper has three sections. In the first section, I introduce the need of a standard in square meters green areas of cities in Peru. I explore how the Covid-19 pandemic can affect the population and public space management, specifically green areas built without any planification. In the second part I reflect on the new typology of green space redesign as a response to the pandemic and prevention for future scenarios that subject populations to mandatory social isolation. In the third part I refer to the affectation of the populations, especially the least favored situations of social isolation due to the distributive injustice of green areas in cities.